Analisis Kepuasan Nasabah Gen Z di Pondok Pesantren Idrisiyyah Tasikmalaya: Mengeksplor Dampak Mobile Banking dan Kualitas Layanan - Meisivi, Fanya; Mubarok, Diki; Sudirman, Iman Fauzi (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study investigates the influence of mobile banking and service quality on customer satisfaction among Generation Z at the Idrisiyyah Islamic Boarding School in Tasikmalaya. The rapid development of digital technology in the financial sector has led to the widespread use of mobile banking as an accessible and efficient platform for conducting banking transactions. Generation Z, having grown up in a digital environment, exhibits strong preferences for banking services that are fast, easy to use, and technologically integrated. At the same time, the quality of service—such as responsiveness, reliability, and security—remains a key determinant of customer satisfaction, even within traditional educational institutions like Islamic boarding schools. This research employed a quantitative approach using a survey method, with a sample of 100 Generation Z students selected from the Idrisiyyah Islamic Boarding School. The data were analyzed using multiple linear regression to assess the individual and joint effects of mobile banking and service quality on customer satisfaction. The results show that mobile banking has a positive and significant partial effect on satisfaction, indicating that ease of use, functionality, and personalization features are highly valued by young users. Furthermore, service quality demonstrated a dominant and statistically significant influence on satisfaction, especially in terms of responsiveness and assurance. Simultaneously, both variables together were found to significantly affect satisfaction levels, reinforcing the importance of integrating high-quality service delivery with digital innovations. The study concludes that improvements in both digital banking applications and service delivery are essential for meeting the expectations of young digital-native customers. Practically, banks should focus on upgrading technical features while also ensuring consistent and empathetic service interactions. Theoretically, the findings contribute to the existing literature by highlighting how user satisfaction is shaped in religious-based educational settings through a combination of digital convenience and service excellence